Current practice of continence advisors in managing faecal incontinence in the United Kingdom: results of an online survey. (5th September 2017) - Leo, C. A.; Maeda, Y.; Collins, B.; Thomas, G. P.; Hodgkinson, J. D.; Murphy, J.; Vaizey, C. J.
Abstract: Aim: To investigate the current practice of continence advisors in the United Kingdom. Method: Continence advisors were contacted by email or letter to participate in a survey. The survey contained 27 questions which addressed the practice of each continence advisor, their knowledge of continence management and the adequacy of their training. Results: Two hundred and twenty‐six out of a total of 448 continence advisors (50.4%), responded. One hundred and seventy (76.9%) advisors treated both faecal and urinary incontinence, 51 (23.1%) treated urinary incontinence. Thirty‐six advisors (16.1%) were lone workers and 130 (58.6%) had more than 10 years' experience. The majority of the advisors (75.6%) performed a digital rectal examination as part of their assessment. Regarding the management of faecal incontinence, 148 prescribed suppositories, 127 offered enemas and 147 advised on rectal irrigation. Most of the advisors taught pelvic floor exercises ( n = 207) and urge resistance techniques ( n = 188). One hundred and fifty‐nine (87.4%) prescribed the Peristeen Coloplast ® anal plug and 78 (47.6%) prescribed the Renew ® anal insert. Eighty‐nine advisors (42.6%) felt they had not been adequately trained to provide a bowel continence service. Conclusion: The majority of continence advisors in the UK manage faecal incontinence. They are able to initiate a broad range of conservative treatment options; however, almost half of the advisors who answered the survey felt inadequately trained and may be better supported by further training.